Prevalence of growth and endocrine disorders in Malaysian children with transfusion-dependent thalassaemia - Tan, Khian Aun; Lum, Su Han; Yahya, Abqariyah; Krishnan, Shekhar; Jalaludin, Muhammad Yazid; Lee, Way Seah (Stamford Publishing Pte Ltd / Singapore Medical Association, 2019)
INTRODUCTION Endocrine dysfunction due to iron overload secondary to frequent blood transfusions is a common complication in children with transfusion-dependent thalassaemia (TDT). We ascertained the prevalence of endocrine dysfunction in children with TDT seen in a hospital setting in Malaysia. METHODS We reviewed all patients with TDT who had ≥ 8 blood transfusions per year. Patients who had a history of stem cell transplantation, concurrent autoimmune diseases or were newly diagnosed to have TDT were excluded. Standard diagnostic criteria were used in the diagnosis of various endocrine dysfunctions. RESULTS Of the 82 patients with TDT, 65% had at least one endocrine dysfunction. Short stature was the commonest (40.2%), followed by pubertal disorders (14.6%), hypoparathyroidism (12.3%), vitamin D deficiency (10.1%), hypocortisolism (7.3%), diabetes mellitus (5.2%) and overt hypothyroidism (4.9%). Subclinical hypothyroidism and pre-diabetes mellitus were seen in 13.4% and 8.6% of the patients, respectively. For children aged < 10 years, the prevalence of both thyroid dysfunction and hypoparathyroidism was 9.1%. CONCLUSION Two-thirds of children with TDT experienced at least one endocrine dysfunction. Thyroid dysfunction and hypoparathyroidism may be missed if endocrine screening is only performed in children with TDT > 10 years of age. Close monitoring for endocrine dysfunction and hormonal therapy is essential to prevent long-term adverse outcomes. © 2019, Singapore Medical Association. All rights reserved.